(untitled) (Journal of Partial Differential Equations, 2016)
In this paper, the auxiliary rational shape is successfully applied for obtaining new exact travelling solutions of the nonlinear lattice equation. These solutions include rational solutions, with periodic and doubly periodic wave profiles. Many new exact traveling wave solutions are successfully obtained.